2006
DOI: 10.1111/j.1440-1746.2006.04505.x
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of endoscopic submucosal dissection over conventional endoscopic mucosal resection

Abstract: Endoscopic submucosal dissection can take a long time, but is superior to conventional endoscopic mucosal resection for treating intramucosal gastric neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
85
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 21 publications
3
85
1
Order By: Relevance
“…Tumor size and resected specimen size were evaluated as risk factors in several studies. Lesion sizes > 10 mm 55 and >20 mm 43,56 were not found to increase PPB in some studies, whereas lesion sizes > 20 mm, 20,22,39,[57][58][59] >30 mm, 39 and >40 mm 58 were found to be associated with higher PPB risk in others. Regarding specimen size, the larger the ulcer, the higher the risk, with an artificial ulcer > 30 mm, 36 34 mm,…”
Section: Risk Factors For Ppbmentioning
confidence: 93%
See 2 more Smart Citations
“…Tumor size and resected specimen size were evaluated as risk factors in several studies. Lesion sizes > 10 mm 55 and >20 mm 43,56 were not found to increase PPB in some studies, whereas lesion sizes > 20 mm, 20,22,39,[57][58][59] >30 mm, 39 and >40 mm 58 were found to be associated with higher PPB risk in others. Regarding specimen size, the larger the ulcer, the higher the risk, with an artificial ulcer > 30 mm, 36 34 mm,…”
Section: Risk Factors For Ppbmentioning
confidence: 93%
“…30,58 However, several studies reported no significant differences in PPB according to tumor location. [14][15][16][17][18][20][21][22][23][24][25][26][27][28][29]32,39,42,43,51,55,61 Horizontal localization (anterior or posterior wall; lesser or greater curvature) was not found to influence PPB in individual studies. [15][16][17][20][21][22][23][24]27,29 Regarding the relationship between…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…5 In contrast to EMR, endoscopic submucosal dissection (ESD) can resect lesions larger than 2 cm en bloc and reduce local recurrence. [6][7][8][9] But ESD may also cause serious complications such as bleeding or perforation more frequently than conventional EMR. [5][6][7]10 As life expectancy has increased because of better living conditions and improvements in the treatment of chronic disease, more patients who undergo ESD have one or more chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Therapies involving ESD have a higher rate of complete resection (R0) and lower rate of local recurrence than conventional EMR [6][7][8][9][10][11]. However, the fact that ESD is carried out for difficult-to-resect tumors has caused the new, though infrequent, problem of post-ESD local residual or recurrent tumors, the characteristics of which are poorly understood.…”
Section: Introductionmentioning
confidence: 99%